The Impact of Recurrent Seizures on Cognitive Functions in Epilepsy: A Literature Review - Yudhisman Imran; Ainaya Az Zahra (CoinReads Media Prima, 2026)
Epilepsy is among the most prevalent chronic neurological disorders, affecting more than 50 million people worldwide and contributing substantially to the global burden of neurological disease. Beyond the seizures themselves, recurrent epileptic activity is increasingly recognized as a driver of progressive cognitive decline; however, cognitive comorbidity remains under-addressed in routine clinical management. This literature review synthesizes current evidence on the mechanisms, clinical manifestations, and assessment of cognitive impairment associated with recurrent seizures. Recurrent seizures arise from an imbalance between excitatory (glutamate) and inhibitory (GABA) neurotransmission, producing neuronal hyperexcitability and hypersynchronization. During and after seizure episodes, cyclooxygenase-2–dependent cerebral vasoconstriction induces localized hypoperfusion and hypoxia; when repeated, these events accumulate, causing structural and functional brain injury. The hippocampus, essential for memory, is particularly vulnerable to hypoxic-ischemic damage, whereas temporal- and frontal-lobe involvement disrupts memory, language, attention, and executive function. Approximately 60–70% of patients with chronic epilepsy experience cognitive impairment, the severity of which is modulated by age at onset, seizure frequency, duration, and antiepileptic drug use. Practical screening tools such as the Montreal Cognitive Assessment (MoCA), including its validated Indonesian version (MoCA-Ina), demonstrate higher sensitivity than the Mini-Mental State Examination for detecting mild impairment, while brain-derived neurotrophic factor represents a promising biomolecular marker of cognitive dysfunction. Collectively, the evidence indicates that epilepsy management should extend beyond seizure control to incorporate routine cognitive surveillance. Early detection through sensitive screening instruments enables comprehensive, individualized treatment planning and may ultimately improve the long-term quality of life for people living with epilepsy.